Leishmania sp. infection in dogs from Florianópolis, Santa Catarina, SC, Brazil - Pacheco, Acácio Duarte; Laurenti, Márcia Dalastra; Lima, Valéria Marçal Félix de; Tomokane, Thaíse Y; Marcondes, Mary [UNESP] (My University, 2013)
The aim of the present study was to investigate the occurrence of Leishmania sp. infection in dogs (N = 491) living in the municipality of Florianópolis, Santa Catarina (SC), Brazil, which was considered a disease-free region for visceral leishmaniasis until 2011, when autochthonous cases of canine disease were notified. Seroprevalence in this population was assessed by ELISA (0.4%; 2/491) and IFAT (4.09%; 24/491). Only one dog exhibited seroreactivity in both serological methods, comprising a total of 25 (5.3%) seroreagent animals. Leishmania sp. DNA, obtained from a sample of whole blood of this animal, was amplified by both conventional and Real-Time PCR. Sequencing of the amplified DNA and, thereby, determination of the Leishmania species involved, was not possible. Our results suggest the necessity of a thorough epidemiological investigation in Florianópolis. (AU).

O objetivo do presente estudo foi pesquisar a ocorrência de infecção por Leishmania sp. em cães (N = 491) domiciliados no município de Florianópolis, Santa Catarina, considerada uma região indene para leishmaniose visceral até o ano de 2011, quando foram notificados casos autóctones da doença canina. A soroprevalência na população foi avaliada por ELISA (0,4%; 2/491) e RIFI (4,09%; 24/491). Somente um cão apresentou sororeatividade em ambos os métodos soro-lógicos, totalizando 25 (5,3%) animais sororeagentes. O DNA de Leishmania sp., obtido de uma amostra do sangue total desse animal, foi amplificado por PCR convencional e PCR em Tempo Real. Não foi possível realizar o sequenciamento do DNA amplificado e, deste modo, determinar a espécie de Leishmania envolvida. Os nossos resultados sugerem a necessidade de uma investigação epidemiológica minuciosa em Florianópolis. (AU).
Infecção por Leishmania sp. em cães de Florianópolis, Santa Catarina, SC, Brasil
Keywords: Animais; Cães; Leishmaniose; Visceral/patologia; Reação em Cadeia da Polimerase; Leishmania/parasitologia; Cães/parasitologia; Ensaio de Imunoadsorção; Enzimática/veterinária